Au(iii) compounds as HIV nucleocapsid protein (NCp7)–nucleic acid antagonists. Issue 1 (18th November 2016) - Spell, Sarah R.; Mangrum, John B.; Peterson, Erica J.; Fabris, Daniele; Ptak, Roger; Farrell, Nicholas P.
Abstract : Interaction of [Au(dien)(9-EtGua)] 3+ abrogates NC binding to cognate SL2 sequence by Zn 2+ displacement by Au. Abstract : The HIV nucleocapsid NCp7–SL2 RNA interaction is interrupted in the presence of a formally substitution-inert gold(dien)-nucleobase/N-heterocycle AuN4 compound where the N-heterocycle serves the dual purposes of a template for "non-covalent" molecular recognition of the essential tryptophan of the protein, mimicking the natural reaction and subsequent "fixation" by Au–Cys bond formation providing a chemotype for a new distinct class of nucleocapsid–nucleic acid antagonist.